Social Capital, Civic Engagement, and Economics in a Transitioning Economy: The Case of Vietnam Provinces. Issue 11 (19th September 2017) - Pink-Harper, Stephanie A.; Duong, Diep
ABSTRACT: Social capitalist assert that civic engagement and participation yield significant economic gains for a county but, generally focus on democratic governed societies. The objective of this research is to determine if social capital transitions to Vietnam, a single-party governed country. This analysis first identifies factors that impact civic engagement and participation. Then it analyzes the relationship between civic engagement, participation, and economics. Using the 2012 Provincial Governance and Public Administration Performance Index, we find human capital is a stronger predictor of economics in Vietnam. We conclude by offering policy implications for understanding social capital in single-party, transitioning economy countries.